2014
DOI: 10.1007/s00894-014-2359-5
|View full text |Cite
|
Sign up to set email alerts
|

Establishing conditions for simulating hydrophobic solutes in electric fields by molecular dynamics

Abstract: Despite considerable effort over the last decade, the interactions between solutes and solvents in the presence of electric fields have not yet been fully understood. A very useful manner in which to study these systems is through the application of molecular dynamics (MD) simulations. However, a number of MD studies have shown a tremendous sensitivity of the migration rate of a hydrophobic solute to the treatment of the long range part of the van der Waals interactions. While the origin of this sensitivity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…This study further suggested that the non-zero force was generated by water molecules belonging to the first two hydration shells. Although, the result is sufficient to conclude that a non-zero force is produced by simple truncation of vdW forces, understanding of water's first two hydration shells causing the non-zero forces has not been achieved [52].…”
Section: The Effect Of Lennard-jones Cutoffmentioning
confidence: 96%
See 2 more Smart Citations
“…This study further suggested that the non-zero force was generated by water molecules belonging to the first two hydration shells. Although, the result is sufficient to conclude that a non-zero force is produced by simple truncation of vdW forces, understanding of water's first two hydration shells causing the non-zero forces has not been achieved [52].…”
Section: The Effect Of Lennard-jones Cutoffmentioning
confidence: 96%
“…A net flux of water has also been observed in an uncharged CNT under an applied uniform electric field [50]. In this case, artifacts related to the treatment of the long-range part of the van der Waals interactions have been reported [51,52]. In particular, Bonthuis et al [45] simulated CNTs with different Lennard-Jones (LJ) cutoff lengths and two different truncation schemes: 1) simple cutoff, which sets the force to zero and the LJ potential to a small constant value beyond a cutoff distance (rc).…”
Section: The Effect Of Lennard-jones Cutoffmentioning
confidence: 99%
See 1 more Smart Citation